Sufism in the Eyes of Muslim Elites in South Sumatra, Indonesia: A Comparison Between Muhammadiyah and Nahdlatul Ulama - Ariadi, Purmansyah; Rulitawati, Rulitawati; Nawi, Muhammad Zainuddin; Asvio, Nova (KALAM, 2021)
This study aims at examining the variety of understanding and implementation of sufistic values among elite members of Islamic mainstream organizations, namely Muhammadiyah and Nahdlatul Ulama, in South Sumatra. It uses a field research method and a descriptive-qualitative analysis. This research finds that elite members of two mainstream Islamic organizations in South Sumatra similarly consider the importance of sufistic values, such as faqr, sabr, tawakkal, ikhlas, and ihsan, for perfecting the self. However, they have differed in how these values are implemented. If the former comfortably practices the substantive forms of sufistic teachings, the latter tends to observe sufistic teachings via the route of tarekat (sufi orders).  Such difference has led to the variety of Islamic practices and dakwah programs organized by both organizations.